CONCEPTS IN THE LINGUO-TERRITORIAL DICTIONARY OF LATGALE - Šuplinska, Ilga (Via Latgalica, 2010)
Particular article is aimed at analysis of data from the questionnaire "Latgola is ...", providing insight into the selected cultural symbols, concepts of the future linguo-territorial dictionary of Latgale. The questionnaire is carried out in April – July 2010, by surveying 1959 inhabitants of the Latgale planning region, at least for 20 years residing in Latgale. Respondents in four age groups (12–25, 26–44, 45–63, 64–80) participated in the poll, among participants of the questionnaire 42.4% were men and 56.9% were women, a relatively high is number of respondents with higher education: 30.3%. Respondents from 20 municipalities of the Latgale planning region and 2 cities of republican significance were interviewed. Size of the general group at 2010 was 339,783 inhabitants.Top tokens of Latgale are related to ethnicity (latgalīts, čangaļs, lobs cylvāks, vasals), religion (Aglyuna, kopusvātki). Characteristic Catholic signs are no longer clearly perceptible and attributable to the formula: if Latgalian, then a Catholic, and vice versa, since both tokens, on the one hand, become secularized, on the other hand, become a symbol of Catholic unity (Aglona) or the family unity (kapusvētki). In the field of Latgale concepts an increasingly important role is devoted to Latgalian language as representative token of recognition of their own and other Latvians.In total 214 tokens can be highlighted, which more than half of the respondents highlighted as concepts being characteristic for Latgale (and therefore in the questionnaire marked by at least 980 respondents). On these tokens also entries in the Latgale linguo- territorial dictionary are based:Names and name combinations to designate historical, cultural or natural facts and phenomena of the Latgale: sādža, šifers, buoba, buorineite, Leivuona stykls, buļvis, Andrejdīna, abādys, zemnīks, muols.Personal names: place-names, anthroponyms: Aglyuna, Daugava, Piters, Boņuks, Visvaļds, Jersika, Grebļa kolns, Dagda, Mūks Roberts, Manteifeļs, Jūrdžs.Titles of artistic works, periodicals, groups: “Cylvāka bārns”, “Bez PVN”, “Deds ar buobu”, “Tauta grib dzeivuot”, “Dziga”, “Gaisma”, “LaKuGa”, “Tik skaidra volūda”.Non-equivalent vocabulary (one that is internationalized or (as the reality designation)) is characteristic to a defined area: šmakovka, gryuslis, cupka, cymuss, sipisnīks, šaļteņa.At the same time one of key purposes of the dictionary is awareness raising of the Latgale Latvians, which means that researchers of the ESF project „Linguo-Cultural and Socio-Economic Aspects of Territorial Identity in the Development of the Region of Latgale” (Nr.2009/0227/1DP/1.1.1.2.0/09/APIA/VIAA/071) in the dictionary concept have left also such signs, which are perhaps not as popular and known to most inhabitants of Latgale, but are important for understanding of the Latgale traits, its originality.Writers of the dictionary hope that the said edition will not only permit to start a new publication series in Latvia, but also to help people from another district to understand and to adopt the differences and for the Latvian from Latgale to find in multicultural environment the most important values generating the Latgale traits.